1-Hydroxypyrido[2, 3-d]pyrimidin-2(1H)-ones as novel selective HIV integrase inhibitors obtained via privileged substructure-based compound libraries. Issue 20 (15th October 2017) - Gao, Ping; Zhang, Lingzi; Sun, Lin; Huang, Tianguang; Tan, Jing; Zhang, Jian; Zhou, Zhongxia; Zhao, Tong; Menéndez-Arias, Luis; Pannecouque, Christophe; Clercq, Erik De; Zhan, Peng; et al.
Abstract: A small library containing 3-hydroxyquinazoline-2, 4(1 H, 3 H )-dione and 1-hydroxypyrido[2, 3- d ]pyrimidin-2(1 H )-one scaffolds was obtained via the copper(I)-catalyzed azidealkyne cycloaddition (CuAAC) reaction and evaluated for their anti-HIV activity in MT-4 cells. Among the synthesized compounds, several 1-hydroxypyrido[2, 3- d ]pyrimidin-2(1 H )-one derivatives showed remarkable anti-HIV potency with EC50 values ranging from 0.92 to 26.85 µM. The most active one, IIA-2, also showed remarkable and selective potency against HIV type 1 integrase (IN). To the best of our knowledge, this is the first report showing that 1-hydroxypyrido[2, 3- d ]pyrimidin-2(1 H )-ones are selective HIV IN inhibitors. Preliminary structure-activity relationship (SAR) studies suggested that the divalent metal ion chelators and the nature and position of substituents around the core are important for antiviral potency. Molecular modeling has been used to predict the binding site of the pyrido[2, 3- d ]pyrimidin-2(1 H )-one core in HIV type 1 IN and suggestions are made for improvement of its inhibitory activity.